Dinamika dan Tantangan Masyarakat Islam di Era Modernisasi - Fitriani Fitriani; Andi Abdul Hamzah; Darussalam Syamsuddin (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2026)
This article discusses the dynamics and challenges faced by muslims in the era of modernization, marked by the rapid development of science, technology, and globalization. Modernization brings varous changes in social, cultural. Economic, and relegious aspects that influence the mindset and behavior of muslim communities. On one hand, modernazation opens great opportunities for the progress of muslims through access to education, technological innovation, and global participation. On the other hand, challenges arise such as identiy crisis, shiffing moral values, secularization, and weak understanding of religious teachings. This article uses a descriptive qualitative approach to analyze how muslims respond to these changes. The results of the study indicate that an adaptive, critical and selective attitude is needed in facing modernization, while still adhering to the principles of islamic teachings. The integration of islamic values and contemporary developments is key to maintaining a balance between progress and religious identity. Thus, muslims can play an active role in building an advanced civilization without losing their spiritual foundation.